Covid-19 management strategies for higher learning institute: A case study in Universiti Malaya / Hazren Mohd - Hazren , Mohd (2022)
COVID-19 affected nearly every country and more than 50 million individuals worldwide. Many businesses and services were unprepared for the effects of COVID-19 on their daily operations. Also affected by the COVID-19 pandemic are Higher Learning Institutions (HLIs). Pandemic management in HLIs requires the deployment of methods based on health, economic, legal, and humanistic considerations. Therefore, in this work, a comprehensive COVID-19 management guideline was developed by taking into consideration the overall operation and activities of the HLI campus. The COVID-19 management guidelines consist of a checklist that covers key aspects and strategies for managing COVID-19 or any other pandemic in HLI in the future. The strategies evaluated the requirements of many stakeholders, including financial and legal considerations. Subsequently, the COVID-19 management guidelines also consisted of detailed procedures from designing and implementing strategies to monitoring and reporting on incidents of the pandemic. The practicality of using the COVID-19 management guideline was validated at the University of Malaya. The result showed that the COVID-19 management guideline is practical as a reference to implementing pandemic management strategies with minimum resource requirements. Hence, the study has demonstrated that the COVID-19 management guidelines established can be used to initiate pandemic management strategies in HLIs.